2006
DOI: 10.1007/s00063-006-1024-x
|View full text |Cite
|
Sign up to set email alerts
|

Stellenwert der Kipptischuntersuchung im Vergleich zum Schellong-Test bei orthostaseinduzierten Kreislaufdysregulationen/Synkopen

Abstract: Schellong's test is suitable as a diagnostic procedure for orthostatic dysregulation only, and tilt-table testing is highly superior for objectification of the diagnosis and differentiation of syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
2
Order By: Relevance
“…In contrast, Werner et al [11] identified a significant association between increased numbers of BM-CPCs and a decreased risk of major cardiovascular events and hospitalization in patients with coronary artery disease. BM-CPCs mobilization can also predict severe endothelial dysfunction in patients with coronary heart disease [36]. Moreover, the transient increase in CD34/45 + and CD133/45 + BM-CPCs reached a maximum after three weeks of regular symptom-limited (ischemic and/or subischemic) exercise training, but did not persist until 3 months after the regular training after acute myocardial infarction [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Werner et al [11] identified a significant association between increased numbers of BM-CPCs and a decreased risk of major cardiovascular events and hospitalization in patients with coronary artery disease. BM-CPCs mobilization can also predict severe endothelial dysfunction in patients with coronary heart disease [36]. Moreover, the transient increase in CD34/45 + and CD133/45 + BM-CPCs reached a maximum after three weeks of regular symptom-limited (ischemic and/or subischemic) exercise training, but did not persist until 3 months after the regular training after acute myocardial infarction [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the population (± SD) was 53 (±19 years), and the median age was 56. The diagnostic setting was previously described in detail [ 10 ] and is summarized below (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The tilt could be controlled using an external protractor that was attached to the table. The head-up tilt device was self-designed as described [ 10 ]. Electrocardiographic (ECG) analysis was continuously performed throughout the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Bei Im Vergleich dazu weist die Kipptisch-Untersuchung eine höhere Sensitivität zum Nachweis einer (insbesondere verzögert auftretenden) orthostatischen Dysregulation auf [19]. Weiterhin kann diese die Bestätigung einer vermuteten vasovagalen Reflexsynkope bzw.…”
Section: Elektrophysiologische Untersuchungunclassified